Protection Effect of Soy Isoflavones (Genistein and Daidzein) on Hematologic Parameters in Acute Kidney Injury: Efek Perlindungan Isoflavon Kedelai (Genistein dan Daidzein) terhadap Parameter Hematologi pada Cedera Ginjal Akut - Mohammed, Hawraa; Abdullah, Asia S.; AL‑Mozie'l, Muhsin S.G. (Academia Open, 2024)
Background: Acute kidney injury (AKI) is a severe, high-morbidity condition with limited effective preventative and therapeutic strategies despite advancements in understanding and treatment. Specific Background: Rhabdomyolysis-induced acute kidney injury (AKI) presents significant challenges in renal research, but soy isoflavones, particularly GN and DZ, have shown potential in mitigating oxidative stress and inflammation. Knowledge Gap: Soy isoflavones, while potentially providing renal protection, their impact on renal and hematologic parameters in glycerol-induced AKI models has not been thoroughly studied. Aims: The study evaluated the effectiveness of soy isoflavones in regulating renal and hematologic parameters in a glycerol-induced AKI rat model, assessing their potential as therapeutic agents. Results: The study involving adult female Wistar rats showed that pretreatment with glycerol or dihydroxystilbene significantly reduced urinary β2-microglobulin, albumin, BUN, and serum creatinine levels in the AKI-induced group, reversing hematological changes. Novelty: The study explores the protective effects of soy isoflavones on renal function and hematologic parameters in AKI, highlighting GN's superior efficacy over DZ. Implications: Soy isoflavones, particularly GN, may be potential preventive or therapeutic strategies for AKI caused by rhabdomyolysis, warranting further research for clinical applications. Highlights: GN and DZ reduce kidney damage in glycerol-induced AKI. GN is more effective than DZ in kidney and blood parameters. Soy isoflavones could treat or prevent AKI. Keywords: Acute kidney injury, soy isoflavones, glycerol-induced AKI, renal protection, hematologic parameters